Effect of caco3 Nanoparticles on the Mechanical and Photo-Degradation Properties of Ldpe - Armijo-Reyes, A; Ortiz-Nunez, J; Zapata-Ramirez, P; Ramirez-Navarro, M; Ramirez-Navarro, M (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
CaCO3 nanoparticles of around 60 nm were obtained by a co-precipitation method and used as filler to prepare low-density polyethylene (LDPE) composites by melt blending. The nanoparticles were also organically modified with oleic acid (O-CaCO3) in order to improve their interaction with the LDPE matrix. By adding 3 and 5 wt% of nanofillers, the mechanical properties under tensile conditions of the polymer matrix improved around 29%. The pure LDPE sample and the nanocomposites with 5 wt% CaCO3 were photoaged by ultraviolet (UV) irradiation during 35 days and the carbonyl index (CI), degree of crystallinity ((c)), and Young s modulus were measured at different times. After photoaging, the LDPE/CaCO3 nanocomposites increased the percent crystallinity ((c)), the CI, and Young s modulus as compared to the pure polymer. Moreover, the viscosity of the photoaged nanocomposite was lower than that of photoaged pure LDPE, while scanning electron microscopy (SEM) analysis showed that after photoaging the nanocomposites presented cavities around the nanoparticles. These difference showed that the presence of CaCO3 nanoparticles accelerate the photo-degradation of the polymer matrix. Our results show that the addition of CaCO3 nanoparticles into an LDPE polymer matrix allows future developments of more sustainable polyethylene materials that could be applied as films in agriculture. These LDPE-CaCO3 nanocomposites open the opportunity to improve the low degradation of the LDPE without sacrificing the polymer s behavior, allowing future development of novel eco-friendly polymers.